Kemampuan Pemecahan Masalh Matematika Ditinjau Dari Minat Belajar Siswa Kelas VIII SMP Negeri 11 Mataram Tahun Ajaran 2024/2025 - Herbianti, Fitri; Sripatmi; Tabita Wahyu, Triutami; Baidowi (FKIP Universitas Mataram, 2024)
This research aims to describe mathematical problem solving abilities in terms of learning interest of class VIII students at SMP Negeri 11 Mataram for the 2024/2025 academic year. This type of research is qualitative descriptive research, which was carried out at SMP Negeri 11 Mataram with class VIII-B research subjects selected using purposive sampling techniques. Data collection techniques use questionnaires, tests and interviews. Data collection techniques used questionnaires, tests and interviews. Based on the results of the study, it shows that there is a relationship between the level of interest in learning mathematics of class VIII students of SMP Negeri 11 Mataram and the ability to solve mathematical problems. So that students with high category interest in learning mathematics and high problem solving abilities are able to carry out all stages of problem solving, students with medium category interest in learning mathematics and high problem solving abilities are able to carry out all stages of problem solving, students with medium category interest in learning mathematics and medium problem solving abilities are able to carry out all stages of problem solving only on some questions, students with medium category interest in learning mathematics and low problem solving abilities are only able to carry out 3 stages of problem solving and students with low category interest in learning mathematics and low problem solving abilities are only able to carry out 3 stages of problem solving.